Enhanced heat transfer in partially open square cavities with thin fin by using electric field - N. Kasayapanand (2018)
Numerical modeling of the electric field effect on the natural convection in the partially open square cavities with thin fin attached is investigated. The interactions among electric, flow, and temperature fields are analyzed by using a computational fluid dynamics technique. It is found that the flow and heat transfer enhancements are a decreasing function of the Rayleigh number. Moreover, the volume flow rate and heat transfer coefficient are substantially improved by electrohydrodynamic especially at low aperture size, high aperture position, and high inclined angle. Surprisingly, the maximum convective heat transfer is obtained at the minimum electrical energy consumption by placing electrodes at a suitable position. The optimum electrode arrangements for both single fin and multiple fins are also achieved. © 2008 Elsevier Ltd. All rights reserved.